FACTORS INFLUENCING THE GROWTH OF CRAFT BUSINESS IN BOGOR CITY - Arini Murwindarti (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
Bogor City has been the tourist destination for a long time, making this sector as the leading sector for the city. Tourism activities in Bogor City encourage the growth of creative industry especially craft business that reap the benefit through direct sales to the tourists as souvenirs. Many argue that unlike other industry in the economy, there are factors that influence the growth of creative industry beside factors of production. This study aims to identify factors that are significantly influencing the growth of craft business in Bogor City. Multiple regression analysis was used to analyze data collected through interviews with 35 owners of craft business which randomly selected from the sample framework. The data obtained including (1) number of workers, (2) capital, (3) raw materials, (4) showroom ownership, (5) participation in exhibitions, (6) business permit ownership, (7) market orientation, and (8) production quantity. The first three data correspond with factors of production in classical economy, while the rest are related to the characteristics of creative-cultural industry. The result shows that none of the variables related to the classical economy factors of production are statistically significant in this model, instead the variables that are related to characteristics of creative-cultural industry are significant. Among other significant variables, participation in exhibition is the most significant variable in affecting the growth of craft business in Bogor City.